Human Sciences? - Armocida, Giuseppe (Medicina Historica, 2019)
In the last few years, we have all been encouraged to read the dedication of University teaching of the History of Medicine in a scientific interest group named “Human Science”. For many of us it seems right to accept this definition that overlooks a variegated horizon that includes many different disciplines, but without leaving the traditional tracks of the disciplinary scientific sector of the History of Medicine.[...]